(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
This study, titled Utilization of Smart Board Technology In Textile Design Instruction For Enhancement Of Performance In Junior Secondary School In Central Senatorial District, Bayelsa State will be carried out to investigate the factors responsible the unavailability of smart boards to teach students in secondary schools in Bayelsa State, Nigeria. Smart board is also known as interactive white board or is a large interactive board display board in the form of a white board. The interesting aspect of the board is that it is electronically operated and pictorial images are usually presented through it. Unfortunately, despite the commendable services smart board renders, it is observed that it is not available especially the teaching of textile in most secondary schools in Bayelsa State. This situation is grossly hampering on students’ academic performance. Thus, in a bid to remedy the situation this study will outlines six objectives, research questions and hypothesis to guide the study. The study will review some cognate literatures in course of the study. Stimulus-response and master learning theories will form the theoretical framework for the study. The study will adopt correlational research design. To test the reliability of the instrument, the Spearman Browns Prophetic Formula will be used to test the result. Mean scores ranked order and standard deviation will be used to analyse the research questions. Pearson’s product moment correlation coefficient will be used as statistical tool to analyse the hypothesis. The four hypotheses postulated will be tested using t-test at 0.05 level of significance. The analysis carried out was discussed. Findings obtained from the study were discussed. The study concludes that the use of smart board to teach textile in secondary is effective and when it is not available it affects students’ performance. Thus, the study recommends that smart board should be provided in schools to encourage effective teaching and learning of textile. This research is believed to have contributed to knowledge because it helped to widen scope of knowledge in the use of smart board in teaching textile.